Development and Evaluation of a Web-Based Geographic Information System (GIS) for Agricultural Land Management Using Agile Extreme Programming: Pengembangan dan Evaluasi Sistem Informasi Geografis (SIG) Berbasis Web untuk Pengelolaan Lahan Pertanian Menggunakan Agile Extreme Programming - Akbar Aulia Rachman; Darsanto; Mukhsin (NUANSA INFORMATIKA, 2026)
Precision agriculture is a modern approach that applies technology to improve efficiency and productivity in the agricultural sector. This study develops a Web Geographic Information System (WebGIS)-based agricultural data management system that integrates spatial and non-spatial data into a single platform. The system supports land mapping, crop age monitoring, planting distribution visualization, and harvest status tracking, and was implemented in the administrative area of Indramayu Regency, Indonesia, as the study site. The system was developed using the Agile Extreme Programming (XP) methodology, which provides flexibility in accommodating user requirements throughout the development process. Functional testing was conducted using the Black Box Testing method to verify that all system features performed as intended. System performance was evaluated using the PIECES framework (Performance, Information, Economy, Control, Efficiency, and Service), resulting in scores of 6.70, 5.97, 5.93, 5.83, 5.93, and 5.97, respectively. The evaluation showed that the system met user expectations, particularly those of farmers, with overall performance rated from good to very good. The proposed system provides an effective solution for improving agricultural land management through integrated and efficient monitoring